EXPLORING THE IMPACT OF REWARDS AND PUNISHMENTS ON STUDENT MOTIVATION IN SPEAKING CLASSES - Ainaya Rahayu; Amaliyah, Neli; Selnistia Hidayani (Algebra : Jurnal Pendidikan, Sosial dan Sains, 2024)
ABSTRACT This qualitative study explores the effects of rewards and punishments on student motivation in speaking classes. Conducted with ten high school students, the research employs semi-structured interviews to gather insights into students' perceptions and experiences with different motivational strategies. The study aims to understand how rewards, such as verbal praise, stickers, the chance to select discussion topics, and punishments, including verbal reprimands and additional assignments, influence students' willingness and enthusiasm to engage in classroom discussions. The findings indicate that rewards significantly boost students' confidence and intrinsic motivation. Participants reported increased engagement and a positive attitude towards speaking activities when they received recognition and incentives. The study also emphasizes the importance of a supportive learning environment. Techniques such as triangulation, member checking, and prolonged engagement enhanced the study’s credibility and trustworthiness. Findings suggest that educators should prioritize positive reinforcement and constructive feedback while minimizing punitive approaches to foster a more motivating and supportive classroom atmosphere. Keywords: Students; Rewards; Punishments.   ABSTRAK Penelitian kualitatif ini mengeksplorasi pengaruh penghargaan dan hukuman terhadap motivasi siswa di kelas berbicara. Dilakukan dengan sepuluh siswa sekolah menengah, penelitian ini menggunakan wawancara semi-terstruktur untuk mengumpulkan wawasan tentang persepsi dan pengalaman siswa dengan strategi motivasi yang berbeda. Penelitian ini bertujuan untuk memahami bagaimana penghargaan, seperti pujian lisan, stiker, kesempatan untuk memilih topik diskusi, dan hukuman, termasuk teguran lisan dan tugas tambahan, mempengaruhi kemauan dan antusiasme siswa untuk terlibat dalam diskusi kelas. Temuan menunjukkan bahwa penghargaan secara signifikan meningkatkan kepercayaan diri dan motivasi intrinsik siswa. Peserta melaporkan peningkatan keterlibatan dan sikap positif terhadap aktivitas berbicara ketika mereka menerima pengakuan dan insentif. Studi ini juga menekankan pentingnya lingkungan belajar yang mendukung. Teknik seperti triangulasi, pengecekan anggota, dan keterlibatan jangka panjang meningkatkan kredibilitas dan kepercayaan penelitian ini. Temuan menunjukkan bahwa pendidik harus memprioritaskan penguatan positif dan umpan balik konstruktif sambil meminimalkan pendekatan hukuman untuk menumbuhkan suasana kelas yang lebih memotivasi dan mendukung. Kata Kunci: Siswa; Hadiah; Hukuman.